Perfection of technique of execution of competition exercises «front todes from Fus» sportsmen category «m-class» in acrobatic rock and and roll - Батєєва [Nataliya Batieieva] Наталія Петрівна; Кизім [Petr Kyzim] Петро Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> analysis developed by the author and the efficiency factor of the author’s. The structure of the performance of acrobatic rock’n’roll qualified athletes consisting of inlet exercise «FUS» – the combined effect of the partner and the partner in supporting the movement and acrobatic elements – unsupported motion of the body partner. The composition of the movements of the structure of the competitive exercise «2/4 salto Front Layout to catch» an acrobatic rock’n’roll. It is established that the determining factor of a successful sporting a pair of compatibility is the same speed of development of physical force when joint action partner and the partner, which is characterized by increments of force that on straightening the angle of the joints biokinematic links. The author developed a new technique efficiency ratio of the competitive exercise «2/4 salto Front Layout to catch». This technique can be recommended for sports with difficult coordination structure movements. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>